Effectiveness of instagram and facebook marketing on the customer path at the aloft bali seminyak hotel during the covid-19 pandemic - Segaradana, I Putu Jimmy; Suastini, Ni Made; Prabawati, Ni Putu Diah (Journal of Business on Hospitality and Tourism, 2022)
The most popular marketing strategy today is marketing through social media. This research was conducted to determine the effectiveness of Instagram and Facebook Marketing on the consumer's customer path at the Aloft Bali Seminyak Hotel during the Covid-19 Pandemic. Data collection techniques used in this research are questionnaires, interviews, and documentation studies. The number of respondents in this study were 70 people. The data analysis technique in this research is Partial Least Square (PLS) analysis with SmartPLS version 3.3.2 software. The results of this study indicate that based on the R2 test, the net R2 value obtained is 0.523 classified as a moderate (moderate) model, these results explain that Instagram and Facebook marketing that are run are quite effective on the customer path during the Covid-19 Pandemic. The effect of endogenous variables on exogenous variables is known based on the value of effect size (f2), which is 0.376. This shows that the influence of the Instagram variable on the customer path is included in the strong category. Meanwhile, the f2 value of the Facebook variable is 0.250 which shows the effect of the Facebook variable on the customer path, including the sufficient category.